Gerusan Lokal yang Terjadi di Hilir Bendung dan Upaya Pengendaliannya - Wisafri - - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2014)
Majarity of damages on the dam construction in Indonesia is caused by continuous local scouring at the end side of the dam construction. It grows and reach its lower/bottorm part. It could results in degradation in the dam operation safety. This local scouring was caused by major water flowing passing the dam where there is a high difference level between the top and the end of the dam. Furthermore, it generates inbalancing water flow speed and additional water turbulence. There are different approachs to prevent such damage, and for example by providing one or more additional construction at the end part of the dam. This structure is designed and installed at the bottom part of the dam. Various empirical functions have been developed to design this structure, and one of them is developed by Lacey. The function is reprsented by D = 0.47 * (Q/F)1/2 (D= scouring depth, Q= Discharge, F= the size of the sand particle). However, that function has some limitation. For examples are the local river and dam construction characteristics. Therefore, it is required to be validated by developing a model of dam contructed in a laboratory. Experiments was undertaken by using the model with different characteristics of water flow in order to investigate the scouring pattern, and than method prefentif work